Effect of Ankle Plantar Flexor Spasticity Level on Balance in Patients With Stroke: Protocol for a Cross-Sectional Study - Mahmoudzadeh, Ashraf (JMIR Res Protoc, 2020)
BACKGROUND: The lower limb spasticity after stroke can affect the balance and gait of patients with stroke. OBJECTIVE: The aim of this study is to assess the effects of ankle plantar flexor spasticity level on balance in patients with stroke. METHODS: Patients with stroke were recruited from neurology and physiotherapy clinics in Tehran, Iran. Based on the level of ankle plantar flexor spasticity according to the Modified Modified Ashworth Scale (MMAS), the eligible patients with stroke were divided into 2 groups: high spasticity (MMAS score≥2) and low spasticity (MMAS score<2). The primary outcome measures were the MMAS scores, Activities-Specific Balance Confidence questionnaire scores, eyes-open and eyes-closed posturography measures, and Timed Up and Go test results. The secondary outcome measures were the ankle passive range of motion and ankle joint proprioception. The t test, mixed model univariate analysis of variance, and Spearman rank correlation were used for statistical analysis. RESULTS: Data collection and statistical analysis are complete. The interpretation of results is underway. We expect the results to be published in winter 2020. CONCLUSIONS: We believe that patients with high ankle plantar flexor spasticity after stroke will demonstrate greater balance dysfunction, which will worsen with impaired proprioception, passive range of motion, and eyes closed. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): RR1-10.2196/16045